Penerjemahan Bahasa Indonesia Ke Bahasa Jepang pada Kosakata Informasi Budaya dalam Objek Wisata di Istana Maimun Medan - Nasution, Laraiba; Hasibuan, Annalisa Sonaria; Mawaddah, Alvy (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2023)
This study discusses the translation of Indonesian into Japanese used in the tourist attractions at the Maimun Palace in Medan's cultural vocabulary. The issue at hand in this study is how to categorize translations from Indonesian, the source language (SL), into Japanese, the target language (BSa). The purpose of this study is to identify the types of translation as well as the translation of Indonesian, the source language, into Japanese, the target language. In this study, a descriptive qualitative method was employed to gather data. The dialogue between one of the tour guides about the history of the Maimun Palace, a well-known tourist destination in the city of Medan, served as the research's source of data. In many ways, Maimun Palace still effectively preserves culture. In that civilization, material culture such as traditional culture, which is concentrated and carefully preserved and which the palace foundation promised to maintain, still holds the values and forms of material culture. According to the findings of this study's data on translation categories, the writer will divide the cultural information vocabulary categories obtained using Newmark's theory (1988), namely there is a category of Material (Artefacts) consisting of from 5 vocabulary in the building field, 4 vocabulary in place field, and 6 vocabulary in equipment field after translating the Indonesian story into Japanese. Also included are the Ecology category, which has 1 geographic vocabulary and 7 environmental/regional vocabulary, and the Social category, which has 4 greeting words, 2 job words, and 1 entertainment word.